Analisis Penerapan Sistem Pembukuan Sederhana Pada Usaha Mikro Kecil Pada Toko Bunga Kurnia - Maria Rosalina Menge; Randy Kuswanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are types of economic activities managed by individuals, community groups, or families. Economic development has a major influence on businesses that are included in the national economic sector. Most of the country's income comes from small-scale economic activities. MSMEs have a very important role in advancing the economy both at the regional and national levels. The purpose of this study is to analyze the implementation of a simple bookkeeping system in micro and small businesses at the Kurnia Flower Shop, East Nusa Tenggara. The method used is a qualitative type with a case study type. Data were collected through interviews. The results show that the Kurnia Flower Shop does not apply the Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) in bookkeeping or financial reports that are still made using a cash basis, namely cash in and cash out manually (recorded in the book) and bookkeeping is done every day.